Gallus domesticus egg-white gel accelerate wound healing after tooth extraction - Puspita, Sartika; Putri, Anggun Kharisma; Mahanani, Erlina Sih (Institute of Computer Science (IOCS), 2025)
Background: Tooth extraction is an action taken to prevent or treat the onset of a disease. However, there are still many complications after tooth extraction, such as a wound healing process that runs slowly and even causes excessive bleeding which can cause death. Gallus domesticus egg-white gel is a medicament that has growth factors that can help the wound healing process run smoothly. Purpose: To determine the number of inflammatory cells involved in the wound healing process after tooth extraction by the application Gallus domesticus egg-white gel. Methods: This research is an experimental laboratory in vivo involving 32 male Sprague dawley rats divided into 4 groups: treatment group (egg-white gel), positive control group (iodine glycerin), negative control group (gel base and saline). Each group will have the left mandibular central incisor extracted under ketamine. All samples were sacrificed on day 3 and 7 for histopathological examination. Results: The Kruskal-Wallis test showed a significance value of 0.00 (p <0.05) meaning that there was a significant difference in the number of inflammatory cells on the 3rd and 7th day. The significance value between treatment groups was 0.320 (p>0.05), which means there was no significant difference between groups. Conclusion: There was a decrease in the number of inflammatory cells in the wound healing process after tooth extraction by application of Gallus domesticus egg-white gel histologically to iodine glycerin on the 3rd and 7th day, but statistically there was no significant difference (p>0.05).